Spacecraft potential control aboard Equator-S as a test for Cluster-II - K. Torkar; K. Torkar; W. Riedler; M. Fehringer; F. Rüdenauer; C. P. Escoubet; H. Arends; B. T. Narheim; K. Svenes; M. P. McCarthy; G. K. Parks; R. P. Lin; et al. (Annales Geophysicae, 1999)
The payload of Equator-S was complemented by the potential control device (PCD) to stabilise the electric potential of the spacecraft with respect to the ambient plasma. Low potentials are essential for accurate measurements of the thermal plasma. The design of PCD is inherited from instruments for Geotail and Cluster and utilises liquid metal ion sources generating a beam of indium ions at several keV. The set-up of the instrument and its interaction with the plasma instruments on board is presented. When the instrument was switched on during commissioning, unexpectedly high ignition and operating voltages of some ion emitters were observed. An extensive investigation was initiated and the results, which lead to an improved design for Cluster-II, are summarised. The cause of the abnormal behaviour could be linked to surface contamination of some emitters, which will be monitored and cured by on-board procedures in future. The mission operations on Equator-S were not at all affected, because of the high redundancy built into the instrument so that a sufficient number of perfectly operating emitters were available and were turned on routinely throughout the mission. Observations of the effect of spacecraft potential control on the plasma remained limited to just one event on January 8, 1998, which is analysed in detail. It is concluded that the ion beam lead to the predicted improvement of the particle measurements even outside the low density regions of the magnetosphere where the effect of spacecraft potential control would have been much more pronounced, and that the similar instruments for the four Cluster-II spacecraft to be launched in 2000 will be very important to ensure accurate plasma data from this mission. Key words. Space plasma physics (active perturbation experiments; spacecraft sheaths · wakes · charging; instruments and techniques)